Excavations at Chester, Roman land division and a probable villa in the hinterland of Deva : excavation at Saighton Army Camp, Huntington, Chester - Wood, Philip N.; Griffiths, David G. (2022)
Excavations carried out by Northern Archaeological Associates (NAA) at Saighton Camp - a former British Army training camp - located to the south of the Roman legionary fortress of Chester (Deva Victrix) revealed important and extensive Roman period remains.